POCUS Diagnosis of Sternal Fractures in Children without Direct Trauma-A Case Series - David Troxler; Johannes Mayr (MDPI AG, 2022)
Sternal fractures in children are rare and tend to be caused by high-energy injury. However, sternal fractures may also be caused by minor and indirect trauma and might therefore not be as rare as previously stated. Ultrasound examination is the method of choice for the diagnosis of sternal fractures. We present three cases of sternal fractures not caused by direct trauma that were presented to our A&E department within a period of only 62 days. All of them exhibited localized tenderness, but none had an associated injury. Children presenting to the A&E unit with musculoskeletal thorax pain should be screened by POCUS for sternal fractures, even if they do not report any direct trauma to the thorax.